Formation of a system of multicriteria indicators for the assessment of office leasing options - Ginevičius, Tomas; Skačkauskienė, Ilona; Stasiukynas, Andrius; Jokšienė, Izolda (International Journal of Strategic Property Management, 2017)
With the growing scope of business and the internationalization of companies, office leasing is becoming an increasingly relevant issue. It has become an integral part of business and affects the results of commercial activities. The methods for the assessment of office leasing options that are available at the moment are imperfect, as they lack complexity and they are not related to the objective of the lease – the improvement of business results, imperfect methods for a quantitative assessment of the lease options, etc. The adequacy of the assessment of lease options largely depends on the system of indicators that is used. The system is formed on the basis of a list of indicators composed from different sources. For the system of indicators to fully reflect the analyzed phenomenon and to be suitable for a quantitative assessment, there have to be not too many or too few indicators in the system. This means that the indicators that are insignificant have to be eliminated from the list. The most precise way to do that is to apply methods of mathematical statistics. The research is based on the analysis of scientific literature and the methods of mathematical statistics.First published online 07 Nov 2016